2019
DOI: 10.3390/biom9020062
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Circulating Serpina3g, Matrix Metalloproteinase-9, and Tissue Inhibitor of Metalloproteinase-1 and -2 with Chronic Obstructive Pulmonary Disease Severity

Abstract: Chronic obstructive pulmonary disease (COPD) is influenced by genetic and environmental factors. A protease-antiprotease imbalance has been suggested as a possible pathogenic mechanism for COPD. Here, we examined the relationship between circulating serpina3g, matrix metalloproteinase-9 (MMP-9), and tissue inhibitor of metalloproteinase-1 and -2 (TIMP-1 and -2, respectively) and severity of COPD. We included 150 stable COPD patients and 35 control subjects in the study. The COPD patients were classified into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
(47 reference statements)
2
19
0
1
Order By: Relevance
“…The MMP-9 concentration and the MMP-9/TIMP-1 ratio were higher in patients with emphysema than in those with other phenotypes. This and other studies have suggested that the MMP-9 concentration and the MMP-9/TIMP-1 ratio are the best predictors of emphysema in COPD patients [ 415 ].…”
Section: Mmps and Timps In Human Diseasesmentioning
confidence: 57%
See 1 more Smart Citation
“…The MMP-9 concentration and the MMP-9/TIMP-1 ratio were higher in patients with emphysema than in those with other phenotypes. This and other studies have suggested that the MMP-9 concentration and the MMP-9/TIMP-1 ratio are the best predictors of emphysema in COPD patients [ 415 ].…”
Section: Mmps and Timps In Human Diseasesmentioning
confidence: 57%
“…Another example of protease−antiprotease imbalance in the development of inflammatory disease occurs in COPD, which is a group of progressive lung diseases, most commonly emphysema and chronic bronchitis [ 415 ]. In a previous study, Uysal et al classified patients with COPD by the severity of symptoms and risk of exacerbation, and they found that elevated plasma levels of MMP-9, TIMP-1, and TIMP-2 correlated with the severity of disease.…”
Section: Mmps and Timps In Human Diseasesmentioning
confidence: 99%
“…The levels of MMP-9 in serum and exhaled breath condensate of COPD patients signi cantly increased [39,40]. Some scholars have considered the MMP-9 concentration and the MMP-9/TIMP-1 ratio are the best predictors for emphysema in COPD patients [41,42]. In T0901317 treated 6 week-group, the level of MMP9 was lower compared to the ozone exposure group.…”
Section: Discussionmentioning
confidence: 99%
“…Mohamed et al found that MMP-9 and TIMP-1 play important roles in the pathophysiology of asthma exacerbation and airway remodeling [ 46 ]. Uysal et al found that MMP-9 concentration and the MMP-9/TIMP-1 ratio are the best predictors of emphysema in patients with COPD [ 47 ]. Overall, the results of that experiment are the same as those reported in an earlier study [ 42 ].…”
Section: Discussionmentioning
confidence: 99%